2016
DOI: 10.1016/j.ijsolstr.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

On the validity of linear elastic fracture mechanics methods to measure the fracture toughness of adhesive joints

Abstract: The analysis of large-scale fracture processes, such as those involved in the fracture of adhesive joints, falls outside the scope of Linear Elastic Fracture Mechanics (LEFM). However, experimental data produced in testing adhesive joints are usually reduced with LEFM methods. The consequent error has not yet been evaluated. In this work, an experimental characterization under pure-mode loading of an FM-300 epoxy film adhesive is presented for different adhesive and adherend thicknesses. The experimental data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…Additionally to composite material itself, the study of alternative bonding techniques has also become a topic of relevance in the industry, taking place of the conventional screws and rivets, which not only increase weight but also deteriorate the components structural capacity because they actuate like a stress concentrator contributing to severe delamination problems 3,4 . In this manner, co-cure, co-bonding and secondary bonding techniques have received special attention in recent years, with emphasis on the last two for allowing more varied project designs, sizes and simpler manufacture 3 , besides lowering or suppressing the stress concentration 5 . The difference between each of them is that in co-cure, two uncured laminates are cured simultaneously, in the presence of an adhesive or not.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally to composite material itself, the study of alternative bonding techniques has also become a topic of relevance in the industry, taking place of the conventional screws and rivets, which not only increase weight but also deteriorate the components structural capacity because they actuate like a stress concentrator contributing to severe delamination problems 3,4 . In this manner, co-cure, co-bonding and secondary bonding techniques have received special attention in recent years, with emphasis on the last two for allowing more varied project designs, sizes and simpler manufacture 3 , besides lowering or suppressing the stress concentration 5 . The difference between each of them is that in co-cure, two uncured laminates are cured simultaneously, in the presence of an adhesive or not.…”
Section: Introductionmentioning
confidence: 99%
“…(a) Load-displacement curves (b) rotation angles vs. crosshead displacement at loading point and (c) Mode I interlaminar fracture toughness results (d) observed and calculated delamination lengthHowever, larger deviations were observed in the measurements for the wet specimens, especially for propagation values. Similar results were also reported and discussed in a recent study of Sarrado at el [145]…”
supporting
confidence: 92%
“…They also compared the use of the LEFM-based method and the J-integral method for analyzing adhesive joints under mode I and mode II loadings. The results showed that the LEFM-based method was not suitable for the analysis of adhesive joints fracture, as it depends heavily on the size of the FPZ [145].…”
Section: Effects Of Marine Environments On the Delamination Behavior mentioning
confidence: 99%
“…All the specimens experienced a sudden failure as the loading curves dropped abruptly after the peak values. The total energy release rate (G T ) was calculated by equations (15), (16) and (17), and the ratio mixity given by equation (18). The J MMB was evaluated using equation (9).…”
Section: Mixed-mode I/ii Interlaminar Fracture Toughnessmentioning
confidence: 99%